مسألة الخصوصية والأمن الرقمي في وسائط التواصل الاجتماعي. - سعدية بن دنيا (Tabayyun)
This study investigates privacy and data protection in social media, highlighting digital privacy as a central issue in the digital age. This matter raises many questions regarding the limits of personal data protection for social media users and digital companies and the potential for hacking, publication, exploitation or sabotage. The problem lies in the integrity of social media companies and their commitment to data confidentiality. The paper thus addresses the challenges of safeguarding the right to privacy and security in digital media and the related political and ethical debates. It goes on to examine how these media companies have relinquished their responsibility to secure and protect personal data and information and enforce the right to privacy.